Assessing renal impairment in treatment-naïve adolescents living with HIV commencing antiretroviral therapy in Zimbabwe. (1st April 2023) - Byers, Bradley W.; Drak, Douglas; Shamu, Tinei; Chimbetete, Cleophas; Dahwa, Rumbidzai; Gracey, David M.
Abstract : Objective: People with HIV (PWH) are increasingly experiencing non-communicable complications, including renal impairment, which are associated with worse clinical outcomes. Limited information exists surrounding renal impairment in paediatric PWH, of which the majority live in sub-Saharan Africa, and further information is required to guide clinical practice. This study describes the prevalence of new or worsening renal impairment in adolescents commencing antiretroviral therapy (ART) in Zimbabwe and associated risk factors. Design: Retrospective cohort study. Methods: Data were collected between January 2010 to January 2019 from the medical records of adolescents aged 12–17 years initiating ART at an outpatient HIV clinic in Zimbabwe. Renal function (estimated glomerular filtration rate, eGFR) was calculated using the Full Age Spectrum formula. Proteinuria was defined as a single urine dipstick score of ≥1+. Potential predictors of renal impairment at follow-up were assessed by logistical regression. Results: Two hundred and sixty-six adolescents were included in analysis. Baseline renal impairment (eGFR < 90 ml/min/1.73 m 2 ) and proteinuria were present in 13% and 7% of the cohort, respectively. After a median of 4.1 years (interquartile range: 1.9–6.9) following ART commencement, mean eGFR increased by 10 ml/min/1.73 m 2 ( P < 0.01), and the prevalence of renal impairment decreased to 8% ( P < 0.01). Baseline renal impairment predicted renal impairment at follow-up (odds ratio [OR] 8.98; 95% confidence interval [CI] 2.81–28.68; P < 0.01). Proteinuria trended towards association with renal impairment at follow-up (OR 4.39; 95% CI 0.95–20.31; P = 0.06). Conclusions: Renal impairment is common in adolescent ART-naïve PWH, and baseline renal impairment is associated with longstanding renal impairment, whereas baseline proteinuria trended towards an association with longstanding renal impairment.